Difficulties and motivations for physical exercise in women older than 65 years. A qualitative study - Yolanda López-Benavente; José Arnau-Sánchez; Tania Ros-Sánchez; Mª Beatriz Lidón-Cerezuela; Araceli Serrano-Noguera; Mª Dolores Medina-Abellán (Universidade de São Paulo, 2018)
ABSTRACT Objective: to identify difficulties and motivations for the practice of physical exercise in women older than 65 years. Method: qualitative study based on the phenomenological theory, with focus groups and in-depth interviews. The nursing staff selected 15 women by intentional sampling using the following criteria: age, time dedicated to physical exercise, independence, and absence of cognitive impairment and contraindication for this activity. Two focus groups were formed (one of them did physical exercise for less than 150 minutes per week and the other at least 150 minutes per week) in addition to conducting five in-depth interviews. Qualitative analysis of the data was performed through transcription, coding, categorization, and verification of results. Results: the difficulties to start and develop physical exercise were circumscribed to the perception of poor health and lack of free time; both circumstances result from care obligation, being represented as a gender imposition. However, the motivations are related to perception of strength, need for socialization, and perception of autonomy and freedom. Conclusions: the ideological representation of gender determines the women's decision to exercise. Knowing the meaning and significance that women give to health and their role in the socio-family environment allows nurses to develop relationships and interventions to encourage the practice of physical exercise.